UJI EFISIENSI PENULARAN VIRUS GEMINI DENGAN SERANGGA KUTUKEBUL (Bemisia tabaci) PADA TANAMAN CABAI - RAHMAYANI, DITA; TAUFIK, MUHAMMAD; SYAIR, SYAIR; BANDE, LA ODE SANTIAJI; ASNIAH, ASNIAH; MALLARANGENG, RAHAYU; BOTEK, MUHAMMAD (Jurnal Agroteknos, 2024)
Chili is one of the important vegetables that are cultivated commercially in tropical countries with various benefits. One of the important diseases of chili plants is jaundice caused by Begomovirus or gemini virus. The disease is transmitted through a whitefly (Bemisia tabaci). The research aims to evaluate the ability and number of whitefly insects that can transmit the gemini virus to chili plants. The research was carried out using a group random design (RAK), 4 treatments each treatment was repeated 5 times. The treatment consisted of no inoculation of whitefly on plants (S0), inoculation of 1 whitefly/plant (S1), inoculation of 3 whitefly/plant (S2) and inoculation of 5 whitefly/plant (S3). The variables observed were vegetative growth, incidence and severity of disease. The presence of the whitefly (B. tabaci) increases the incidence and severity of jaundice and inhibits growth in cayenne pepper plants (C. annuum). The transmission of the gemini virus is faster with the inoculation of 5 ticks/plant with the highest incidence and severity of the disease.